2016
DOI: 10.1364/ol.41.000765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of femtosecond photo-treatment on inscription of fiber Bragg gratings

Abstract: Pre- and post-treatment of optical fibers is typically used to improve the fiber Bragg grating (FBG) fabrication process. Here, we investigate experimentally the effects of femtosecond photo-treatment on the ability to inscribe and erase FBGs in standard, non-sensitized, silica SMF fibers. We observe "immunity" to inscription after applying a suitable pre-treatment to the fiber and full "erasure" of the FGB after applying a suitable post-treatment. We characterize the required photo-treatment parameters and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We have found that femtosecond photo pre-treatment can immunize a fiber up to a certain illumination intensity [94]. In fact, the reported multiphoton ionization and inscription threshold ($ 10 13 W=cm 2 ) can be raised so that permanent Bragg gratings first appear at a higher pulse energies.…”
Section: Immunization To Femtosecond Inscriptionmentioning
confidence: 93%
“…We have found that femtosecond photo pre-treatment can immunize a fiber up to a certain illumination intensity [94]. In fact, the reported multiphoton ionization and inscription threshold ($ 10 13 W=cm 2 ) can be raised so that permanent Bragg gratings first appear at a higher pulse energies.…”
Section: Immunization To Femtosecond Inscriptionmentioning
confidence: 93%
“…After the PM is translated 0.635 mm away from the fiber, a second FBG is inscribed exactly at the same spot. The second FBG is inscribed with a higher pulse energy of 330 µJ for 40 s. A higher pulse energy is needed since the refractive index is already modified at this inscription position area, and, thus, the fiber is more immune to refractive index modifications 16,17 . The result of this inscription is a second FBG with a transmission dip of −9 dB at a center Bragg wavelength of ~1553.2 nm as shown in Figure 3.…”
Section: Femtosecond Inscription Of An Array Of Four Fbgsmentioning
confidence: 99%
“…Femtosecond inscription of phase-shifted gratings has been demonstrated using this technique 15 . Finally, with pre and post fs treatments, the Bragg wavelength, λB, can be tuned by modifying the effective refractive index, neff [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Before the experiment, we apply an "immunization" procedure, as described in [25]. We scan the fiber 20 μm around the fiber core, in a direction perpendicular to the fiber and the optical axis of the pump beam, with a uniform line pattern (8.5 mm × 6 μm) and 1 mJ pulse energy (∼6 • 10 13 W∕cm 2 ) for 1.2 M pulses.…”
mentioning
confidence: 99%
“…(Color online.) Spectrum of the permanent FBGs measured at the end of the experiments (after 150 K pulses) with the fs laser pretreatment (solid red line) versus a typical grating without fs laser pre-treatment (150 K pulses, 180 μJ pulse energy; dashed blue line) taken from [25].…”
mentioning
confidence: 99%